Antiviral Nanomedicine-based approaches against Epstein-Barr virus infection - Abdelmonem, Mohamed; Che Abdullah, Che Azurahanim; Bastawecy, Iman M.; Raof, Amal M. A. (2024)
Purpose of Review: The Epstein-Barr virus (EBV) is a common virus around the globe with approximately 98% of adults testing positive against EBV. However, EBV infection typically begins early in the childhood. Owing to the ability to infect various body organ, EBV is linked to a broad spectrum of symptoms, diseases, and inflammatory conditions. Moreover, since EBV exists in both latent and replicating forms in most healthy individuals, any disruption in the balance between the virus and its host can lead to the development of different diseases, including autoimmune disorders and cancer. Given these circumstances, we draw attention to the crucial need for developing prophylactic measures and treatments for EBV and its associated diseases. Recent Findings: We propose leveraging the advantages of nanomedicine, such as ferritin and iron oxide nanoparticles, for the creation of EBV vaccines. These advancements can also be applied to developing drugs to treat EBV-associated diseases, such as cancer, autoimmune disorders, and cytokine storm syndrome. Summary: We emphasize the urgency of having accessible EBV vaccines, as well as effective treatments for EBV-related diseases, especially when early diagnosis is involved. This approach, which includes comprehensive cytokine profiling for patients, can significantly enhance the effectiveness of treatment programs.